2013
DOI: 10.2478/10004-1254-64-2013-2366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychosocial Strain on Back Symptoms in Tehran General Hospital Nursing Personnel

Abstract: Nursing is a stressful and highly demanding job. The aim of this study was to investigate the association between psychosocial job strain and the prevalence of back symptoms in nursing personnel using the demand-control model. In a cross-sectional study, 545 nursing professionals answered to a self-administered questionnaire on demography, job content, and lower and upper back symptoms (LBS and UBS, respectively). Based on their answers, the participants were grouped as follows: low strain, high strain, active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
(27 reference statements)
5
12
1
5
Order By: Relevance
“…These findings do confirm the results from previous studies that psychologically stressful work may increase the musculoskeletal symptoms in the neck shoulder and upper and lower back (7,16). Role related stressors were related to musculoskeletal complaints.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings do confirm the results from previous studies that psychologically stressful work may increase the musculoskeletal symptoms in the neck shoulder and upper and lower back (7,16). Role related stressors were related to musculoskeletal complaints.…”
Section: Discussionsupporting
confidence: 83%
“…Previous research in a large hospital applying a questionnaire includes both task level and social and organizational factors and reported a significant association between psychosocial factors and self reported musculoskeletal symptoms at various body sites among Iranian nurses (16).…”
Section: Introductionmentioning
confidence: 99%
“…; Golabadi et al. ). Both the inability and ability to control daily lives correlated with the occurrence of LBP.…”
Section: Discussionmentioning
confidence: 96%
“…The fact that LBP has most frequently been reported among nurses is well documented (Golabadi et al. ; Rahimi et al. ; Yassi & Lockhart ).…”
Section: Introductionmentioning
confidence: 99%
“…In China the prevalence of MSDs in hospital nurses was found to be as high as 70%, whereas in a study from Japan, only 37% of nursing aides reported some types of MSDs. In our country, Iran, the findings of several studies showed that the preva- lence of MSDs in hospital nurses varied between 46 and 88% (6,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%